The decline of social ROI - González-Fernández-Villavicencio, Nieves (Anuario ThinkEPI, 2014)
In the context of managing social media, metrics showing only financial return on investment (ROI) are losing ground to those that show social media´s primary value as a powerful platform for audience-building and customer relations and conversations. Well-known marketing associations are proposing indicators to monitor the value of Reach, Activity, Engagement, Competitive Analysis, and Sentiment in measuring the relationship in social media between the brand (e.g., libraries) and the users.
Keywords: Metrics; Social media; Libraries; ROI; Value.